2015
DOI: 10.1056/nejmoa1402556
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Device to Narrow the Coronary Sinus in Refractory Angina

Abstract: T h e ne w e ngl a nd jou r na l o f m e dicine n engl j med 372;6 nejm.org february 5, 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
196
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(220 citation statements)
references
References 37 publications
(26 reference statements)
11
196
1
1
Order By: Relevance
“…15 One reason for the dearth of real placebo trials in device studies is the incidence of procedure related complications and the ORBITA study illustrates the inherent risks. Of the 95 patients in the 'placebo' arm, 4 had wire related complications, necessitating bail out PCI, while 2 sustained post procedural major bleeding -a clinically signifi cant complication rate requiring intervention of 6.3%.…”
Section: Ischaemia Versus Symptom Guided Revascularisationmentioning
confidence: 99%
“…15 One reason for the dearth of real placebo trials in device studies is the incidence of procedure related complications and the ORBITA study illustrates the inherent risks. Of the 95 patients in the 'placebo' arm, 4 had wire related complications, necessitating bail out PCI, while 2 sustained post procedural major bleeding -a clinically signifi cant complication rate requiring intervention of 6.3%.…”
Section: Ischaemia Versus Symptom Guided Revascularisationmentioning
confidence: 99%
“…Despite the use of newer antianginal therapy (ranolazine), a large number of patients remain highly symptomatic with impaired quality of life. Verheye et al recently reported the use of a novel balloon-expandable device placed within the coronary sinus to cause of a focal narrowing, thereby increasing pressure within the coronary sinus and theoretically redistributing blood flow to ischaemic myocardium 22 23. In a small clinical trial of 104 patients with Canadian Cardiovascular Society (CCS) class III or IV angina, use of the device relative to a sham procedure was associated with a marked improvement in CCS angina class.…”
Section: Stable Cadmentioning
confidence: 99%
“…In a recent randomized, controlled trial, the coronary sinus restrictor significantly reduced the angina class vs. the control group at 6 months. 54 Clearly, this intervention requires more evaluation.…”
Section: Transmyocardial Revascularizationmentioning
confidence: 99%